The Role of Collagen IV and Neopterin in Iraqi Patients with Cushing’s Disease - Khudhur, Shaimaa Dheyhaa; Jasim, Rasha Zuhair (Journal of Pharmacology and Drug Development, 2025)
Objective: The aim of the present study is to investigate the relationship between the biochemical parameters (collagen IV and neopterin) and the etiology of Cushing's disease in Iraqi patients and to examine the biochemical action of the treatment (prednisolone and hydrocortisone) on the biochemical parameters (cortisol, ACTH, collagen IV, and neopterin). Methods: The patients were classified into four groups: G3 composed of (25) newly diagnosed males with Cushing’s disease / without treatment, G4 composed of (25) newly diagnosed females with Cushing’s disease / without treatment, G5 composed of (25) males with Cushing’s disease / under treatment with prednisolone and hydrocortisone and G6 composed of (25) females with Cushing’s disease / under treatment with prednisolone, Cushing’s patient were compared with healthy subjects with approximately the same range of age-matched with the patients and regarded as two control group: G1 composed of (25) healthy males and (G2) composed of (25) healthy females. The levels of all parameters were determined in sera of both patients and control groups. Results: Statistically, the level of cortisol and neopterin were highly significantly increased, ACTH level was significantly increased and collagen IV was highly significantly decreased in G3 and G4 compared with G1 and G2 respectively, the levels of cortisol and neopterin were decreased (non-significantly for males and significantly for females regarding cortisol, highly significant for males and significantly for females regarding neopterin ) in G5 and G6 compared with G3 and G4 respectively while the same treatment caused a side effect on both ACTH and collagen IV. Cortisol level was a highly significant increase in newly diagnosed females compared with males while the difference was non-significant regarding ACTH, Collagen IV, and neopterin. Conclusion: The current study submits novel findings by elucidating that collagen IV and neopterin show promise as novel biochemical markers for CD. Also, it highlights the reactive action of prednisolone and hydrocortisone in shifting cortisol and neopterin into the balance and the side effects and non-significant effects of these drugs on ACTH and collagen IV respectively.